Evaluation of V-Y versus rotational flaps for sacral pressure sore reconstruction: a comparative study - Sainio, Vilma (My University, 2022)
Coverage of pressure sores in the sacral area can be performed with different types of flaps. Little knowledge is available on which flap design is better than another. Available local flaps should be preserved as far as possible for these patients are susceptible of pressure sore recurrence. The aim of this study was to compare the V-Y flap versus the gluteal rotation flap for sacral pressure sore reconstruction. Methods All patients who had sacral pressure sores of grades III–IV underwent reconstructions with V-Y flaps or gluteal rotation flap were retrospectively reviewed. Patients were divided into two groups according to the flap performed. The primary outcome measure was the surgical site occurrence (SSO). Secondary outcome measures were the length of hospital stay (LOS), specific postoperative complications and recurrence incidence. Results A total of 75 patients were included in the study: 34 patients in V-Y group and 41 patients in rotational flaps group. No significant differences between the study groups were found in respect to demographics, comorbidities, defect sizes and complications (according to Clavien-Dindo Classification). Similarly, no differences were noticed in the length of hospital stay. There was a similar rate of SSOs in both groups (38.2 % vs 39.0 %, p = 0.944). Although not statistically significant, a trend toward reduction of seroma occurrence, blood transfusion need, and longer time to recurrence was detected (0.0% vs 9.8%, p=0.061; 0.0% vs 12.5%, p=0.058; and 57 vs 48 days p=0.846, respectively), favoring V-Y flaps. Conclusion Both flap patterns are safe and reliable for sacral pressure sore defect coverage. Gluteal rotational flaps seem to be associated to a higher seroma occurrence, blood transfusion need and shorter time to recurrence. Complication rates are very comparable in both designs; thus, they can be used at surgeon's preference.
Keywords: Fasciocutaneous flap, Rotational flap, Sacral pressure sore, V-Y flap